Factors Influencing Malnutrition in Patients with End-Stage Renal Disease Undergoing Continuous Ambulatory Peritoneal Dialysis - Pongpen, Siraprapa; Wiseso, Wipa; Chantamit-O-Pas, Chutima (Journal of health and health management, 2026)
This predictive study aimed to examine factors influencing malnutrition and to determine the predictive power of dietary behaviour, oral and dental health conditions, depression, and social support on malnutrition in patients with End-Stage Renal Disease (ESRD) undergoing Continuous Ambulatory Peritoneal Dialysis (CAPD). The sample consisted of 119 patients who had undergone CAPD for at least three months at five peritoneal dialysis clinics in Chonburi Province, selected using purposive sampling. Data were collected using six instruments: a demographic questionnaire and tools assessing dietary behaviour, oral and dental health conditions, depression, social support, and malnutrition. The content validity index ranged from 0.90 to 1.00, and reliability coefficients were 0.84, 0.88, 0.80, 0.96, and 0.71, respectively. Data were analysed using descriptive statistics and stepwise multiple regression. The results indicated that dietary behaviour, oral and dental health conditions, and depression were significantly associated with malnutrition (r = .358, r = -.246, r = -.158, respectively; p < .05). Depression and dietary behaviour were identified as significant predictors of malnutrition, jointly accounting for 14% of the variance (Adjusted R² = .14, p < .001). Depression was the strongest predictor (β = .32, p < .001), followed by dietary behaviour (β = -.18, p < .05). These findings highlight the importance of screening for depression and promoting appropriate dietary behaviour to reduce the risk of malnutrition in CAPD patients.